PepSeq as a highly multiplexed platform for melioidosis antigen discovery and vaccine development - Elko, Evan A.; Williamson, Charles H. D.; Green, Heather R.; Gates-Hollingsworth, Marcellene A.; Nelson, Georgia A.; Pandit, Sujata G.; Mead, Heather L.; Allender, Christopher; Woerle, Celeste; Mayo, Mark; Currie, Bart J.; AuCoin, David P.; et al. (Frontiers in Immunology, 2025)
IntroductionVaccination aims to prevent or mitigate disease by priming the immune system prior to infection. While historical vaccine development relied mostly on trial-and-error, modern approaches have become more directed. By leveraging our growing understanding of pathogen biology and immune correlates of protection, we can design vaccines in ways that promote protective responses. However, the complexity of many pathogens (e.g., bacteria and fungi), as well as our immune responses against them, continue to present important challenges for vaccine development.AimHere, we demonstrate the utility of the PepSeq platform for highly multiplexed serology to both broadly and finely characterize antibody responses against complex pathogens, using the bacterium, Burkholderia pseudomallei, as a case study.MethodsWe designed and synthesized three diverse pools of DNA-barcoded peptides (i.e., PepSeq libraries) and used them to characterize antibodies against a variety of B. pseudomallei proteins.ResultsEpitope-resolved antibody binding profiles were generated for 85 individuals with culture-confirmed melioidosis, 89 US blood bank controls, and 6 monoclonal antibodies. Using these data, we identify novel B cell antigens/epitopes and finely characterize the epitopes of three monoclonal antibodies against the B. pseudomallei GroEL protein.ConclusionHighly multiplexed serology platforms, like PepSeq, enable more comprehensive characterization of antibodies, both polyclonal and monoclonal, which can aid in the development of vaccines, diagnostics and therapeutics, even for pathogens with large, complex genomes.